'Illustrated Picturesquely and Architecturally in Photography': William J. Stillman and the Acropolis in Word and Image. Issue 1 (24th December 2015) - MacManus, Dervla; Campbell, Hugh
Abstract : In 1870, the American William J. Stillman — diplomat, journalist, painter and photographer — published an album of autotypes entitled The Acropolis of Athens: Illustrated Picturesquely and Architecturally in Photography . For a newcomer to the medium, Stillman's images were remarkable for their poise and clarity. But where the photographs were 'clear and lively', to borrow John Szarkowski's phrase, the brief text which accompanied each was, by comparison, laborious and lifeless. Facing each other across each double-spread, text and image seemed to speak in completely different registers, in a manner which presaged many subsequent uses of similar material, most famously Vers une architecture . This article explores the relationship between word and image at play in Stillman's The Acropolis in terms of Stillman's intentions and the genre of the photo-book, and considers the implications that this book, as object and genre, has for word-image relationships within architectural history.